The Role of Stakeholder Pressure and Digital Transparency in Enhancing Carbon Emission Disclosure: Evidence from Indonesian LQ45 Companies - Emy Dwi Nursulistyo; Gustita Arnawati Putri (Jurnal Riset Akuntansi, 2026)
This study examines the effect of stakeholder pressure and digital transparency on carbon emission disclosure among companies listed in the LQ45 Index in Indonesia from 2020 to 2024. As sustainability issues receive increasing attention, companies are expected to provide more transparent environmental information. This study employs a quantitative approach using secondary data collected from annual reports and sustainability reports. The sample was selected through purposive sampling, resulting in 12 companies and 60 firm-year observations. Panel data regression analysis was conducted using EViews 10. The results indicate that stakeholder pressure and digital transparency significantly influence carbon emission disclosure. Companies facing greater stakeholder pressure and demonstrating higher levels of digital transparency tend to disclose carbon emission information more comprehensively. These findings highlight the importance of stakeholder influence and digitalization in promoting corporate environmental accountability. This study contributes to the sustainability accounting literature by providing empirical evidence on the determinants of carbon emission disclosure in companies operating in an emerging market context.